2022
DOI: 10.1155/2022/8245614
|View full text |Cite
|
Sign up to set email alerts
|

Liensinine Inhibits Osteosarcoma Growth by ROS-Mediated Suppression of the JAK2/STAT3 Signaling Pathway

Abstract: Osteosarcoma (OS) is the most common malignancy of bone. Liensinine exerts antitumor effects on cancers of the colon, breast, and gallbladder. However, its antitumor activity in OS remains unclear. This study is aimed at investigating the efficacy of liensinine against OS and the underlying mechanism of action. Cell proliferation, apoptosis, and cycle arrest in OS were detected using the Cell Counting Kit-8 (CCK-8), colony formation, and flow cytometry assays, respectively. The production of reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…It was hypothesized that ROS may also serve a crucial role in development of osteosarcoma. Jia et al revealed that liensinine inhibits osteosarcoma growth by ROS-mediated suppression of the JAK2/STAT3 signaling pathway ( 35 ) and Rawat and Nayak ( 36 ) reported that Piperlongumine induces ROS-mediated apoptosis by transcriptional regulation of SMAD4/P21/P53 genes and synergizes with doxorubicin in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that ROS may also serve a crucial role in development of osteosarcoma. Jia et al revealed that liensinine inhibits osteosarcoma growth by ROS-mediated suppression of the JAK2/STAT3 signaling pathway ( 35 ) and Rawat and Nayak ( 36 ) reported that Piperlongumine induces ROS-mediated apoptosis by transcriptional regulation of SMAD4/P21/P53 genes and synergizes with doxorubicin in osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that liensinine may be associated with the induction of tumor cell apoptosis. 22,24 Therefore, we examined apoptosis in ICC cells following liensinine treatment. However, we found that liensinine did not significantly induce apoptosis in ICC cells, and apoptosisrelated proteins showed no significant trend in Western blot analysis (Figures S1C,D).…”
Section: Liensinine Reversed the Emt Phenotype Of Icc Cells With High...mentioning
confidence: 99%
“…20 In 2015, it was the first time that liensinine was identified as an autophagy/mitophagy inhibitor that could inhibit the growth of breast cancer. 21 Besides, this alkaloid has also been demonstrated to inhibit growth of osteosarcoma cells, 22 gallbladder, and colon cancer cells, 23,24 The secondary antibodies were purchased from BioSharp. HIF-1a overexpressed plasmid was from Genechem.…”
mentioning
confidence: 99%
“…This material shows intriguing photoluminescent properties in the visible range [ 21 ], which, combined with the capability of producing ROS, make the hybrid ZrO 2 a powerful theranostic material for cancer therapy. In particular, the generation of ROS has been used as a synergistic process in the treatment of osteosarcoma (OS) to increase the efficacy of chemotherapeutic drugs [ 22 ]. OS is a bone cancer occurring most often in children and young adults between the age of 10 and 20 years [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the overexpression of surface molecules on the OS cells, including CD44, the major hyaluronic acid (HA) receptor [ 27 ]. The binding between CD44 and HA has been proven to be involved in multidrug resistance [ 28 ], tumor progression, metastasis, and proliferation [ 22 ]. Numerous ROS-generating NPs targeting CD44 + cells have been proposed [ 23 , 29 , 30 ], but, to the best of our knowledge, none of them combines imaging and therapy in a label-free and light-independent approach, such as our ZrO 2 -acac NPs.…”
Section: Introductionmentioning
confidence: 99%